Social Capital Mediates the Relationship between Social Distancing and COVID-19 Prevalence in Japan - Keisuke Kokubun PhD; Yoshinori Yamakawa PhD (SAGE Publishing, 2021)
The threat of coronavirus disease (COVID-19) is increasing. Regarding the differences in the infection rate observed in each region, additionally to studies investigating the causes of differences in population density as a proxy for social distancing, an increasing trend of studies investigating the causes of differences in social capital has also been seen (ie, value sharing, acceptance of norms, unity, and trust through reciprocity). However, studies investigating whether social capital that controls the effects of population density also influences the infection rate are limited. Therefore, in this study, we analyzed the relationship between infection rate, population density, and social capital using statistical data of Japan's every prefecture. Statistical analysis showed that social capital not only negatively correlates with infection rates and population densities, but also negatively correlates with infection rates controlling for the effects of population density. Additionally, controlling the relationship between the variables by mean age showed that social capital had a greater correlation with infection rate than population density. In other words, social capital mediates the relationship between population density and infection rates, indicating that social distancing alone is not enough to deter coronavirus disease; social capital needs to be recharged.